Mekanisme Penyusunan LKD Sesuai dengan SAKD di BKAD Kabupaten Sleman - Saputri, Evieana Riesty (Department of Accounting-Faculty of Economic and Business (FEB), 2023)
This study aims to obtain an overview of the mechanism for preparing regional financial reports in accordance with SAKD at the BKAD of Sleman Regency and also to find out the problems/obstacles that often occur when preparing financial reports at the BKAD of Sleman Regency. This study uses a qualitative method where the researcher uses several methods to collect correct and reliable information related to the study to be discussed, namely the method of interviews, observations, studies and literature. This research can be concluded that with the existence of SIKD local governments can present regional financial information including budgeting activities, budget implementation, and budget preparation which are then announced to the public.